Coaches' perceptions of Canada's national coaching certification program (NCCP): Awareness and value - Misener, K. E.; Danylchuk, K. E. (International Journal of Sports Science and Coaching, 2009)
In Research Notes, Katie Misener and Karen Danylchuk examined coaches` perceptions of Canada`s National Coaching Certification Program (NCCP). It was found that more than half of the 285 participants in their study perceived the value of the NCCP as"good", and this perceived value increased after taking a course. On the basis of their results, the authors recommend that: The Coaching Association of Canada, as well as other coaching education bodies around the world, should consider integrating a strategic "buzz marketing" approach that encourages coaches who have taken NCCP courses to discuss their experience with other coaches in their sport clubs, particularly when program changes occur and organizations need to "get their message out" efficiently and effectively. Buzz marketing has been defined as "capturing attention of consumers and the media to the point where talking about your brand becomes entertaining, fascinating and newsworthy" . The authors conclude that: "Coaching education programs must seek to establish their `brand` as one that adds value to a coach`s overall development and is a necessary aspect of participation in coaching".